Interação Universidade Empresa: um estudo do ecossistema da microrregião de Campo Mourão - Mantovanni, Cibele (2021)
From a systemic perspective, University-Enterprise Cooperation (U-E) has been a great challenge, where the speed of changes in corporate and academic environments are necessary and require significant changes so that innovations in companies gain speed. Thus, this study aimed to analyze how companies in the Microregion of Campo Mourão assimilate and promote U-E cooperation considering innovation and technology sharing. We sought to investigate which actions in the companies' view facilitate the U-E interaction; an identity which are the determining factors that influence the interactions of business organizations with universities, and analyze the main barriers faced by companies regarding U-E cooperation. The methodology adopted was the qualitative approach and the nature of the descriptive study, we applied the strategy of multiple case studies and data collection through interviews with a semi-structured script, fourteen participants were interviewed, twelve companies, three that developed projects of cooperation with the university and nine companies without any cooperation link, the Manager of the Technological Innovation Center of a Federal HEI and representatives of the Economic Development Council of the region. It should be noted that it was considered important to bring the perspective of companies without cooperation to the study, considering that they can contribute to understanding which aspects are obstacles or barriers to U-E cooperation. As a result of the analyses, it was observed that the interaction relationships between the participants are still quite shy and that the work arising from the HEI is still incipient, and there is a path of great challenges to follow, especially in terms of culture regarding interaction (within the university). Regarding the motivators, these positively influenced the interaction, given the aspects presented by the participants. As for the barriers and facilitators of the U-E interaction, it was found that they negatively influenced the U-E cooperation process, emphasizing aspects that discouraged the process. As for the theoretical model proposed in this study, it allowed us to realize that the U-E relationship occurs, but is limited. It was concluded that the companies in the Campo Mourão’s microregion, assimilate that U-E cooperation can transform the region's innovation ecosystem, but they do not promote it due to the lack of incentive and approximation between the participants. In terms of theoretical contributions, this study aimed to generate an understanding of the EU interaction process, based on theoretical models existing in the literature, and as practical contributions, this research presents empirical findings that can contribute to the actors involved in recognizing the dynamics of the process and the innovative potential of the researched region. As a practical contribution, the results will be compiled into an executive summary and presented to research participants and other interested parties, to bring together the participants and minimize the asymmetry of information about the possibilities of U-E cooperation.